Umbilical Cord-Derived Mesenchymal Stem Cells Are Able to Use bFGF Treatment and Represent a Superb Tool for Immunosuppressive Clinical Applications - Tesarova, Lenka; Jaresova, Klara; Simara, Pavel; Koutna, Irena (International journal of molecular sciences, 2020)
Mesenchymal stem cells (MSCs) have become a promising tool in cellular therapy for restoring immune system haemostasis; however, the success of clinical trials has been impaired by the lack of standardized manufacturing processes. This study aims to determine the suitability of source tissues and culture media for the production of MSC-based advanced therapy medicinal products (ATMPs) and to define parameters to extend the set of release criteria. MSCs were isolated from umbilical cord (UC), bone marrow and lipoaspirate and expanded in three different culture media. MSC phenotype, proliferation capacity and immunosuppressive parameters were evaluated in normal MSCs compared to primed MSCs treated with cytokines mimicking an inflammatory environment. Compared to bone marrow and lipoaspirate, UC-derived MSCs (UC-MSCs) showed the highest proliferative capacity, which was further enhanced by media supplemented with bFGF, while the cells maintained their immunosuppressive characteristics. Moreover, UC-MSCs expanded in the bFGF-enriched medium were the least sensitive to undesirable priming-induced changes in the MSC phenotype. Surface markers and secreted factors were identified to reflect the cell response to inflammatory priming and to be variable among MSCs from different source tissues. This study demonstrates that UC is a favorable cell source for manufacturing MSC-based ATMPs for immunosuppressive applications. UC-MSCs are able to use the bFGF-enriched medium for higher cell yields without the impairment of immunosuppressive parameters and undesirable phenotype changes after inflammatory preconditioning of MSCs before transplantation. Additionally, immunosuppressive parameters were identified to help finding predictors of clinically efficient MSCs in the following clinical trials.
Keywords: Fibroblast Growth Factor 2; Mesenchymal Stem Cells; Humans; proliferace buněk; Cell Differentiation; lidé; buněčná diferenciace; mezenchymální kmenové buňky; Umbilical Cord; imunosupresivní léčba; Immunosuppression Therapy; fibroblastový růstový faktor 2; pupečník; Cell Proliferation